The Awareness Assessment Model: measuring the awareness and collaboration support over the participant’s perspective - Mantau, Márcio J.; Benitti, Fabiane B. V. (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2023: Anais do XVIII Simpósio Brasileiro de Sistemas Colaborativos, 2023)
[Context] Awareness has been a valuable concept in Collaborative Systems since its formation, being an essential part of groupware. The efficient awareness mechanism ensures a better understanding and, consequently, a better projection of future actions; in contrast, the lack of these mechanisms undermines comprehension and prevents participants from projecting their work accordingly. [Problem] This is a multi-factorial problem, and finding a goodm starting point in the literature can be challenging for novice groupware designers; they must reinvent awareness from their own experience of what it is, how it works, and how it is used. [Goal] This work consists of establishing an assessment model for collaborative interfaces by analyzing the awareness mechanisms provided from the participant’s viewpoint. Our awareness assessment model developed adopting the statistical technique Item Response Theory (IRT) and considers the participant’s skill in understanding the awareness and the difficulty involved. [Results] The proposed assessment model allow us to measure the awareness support provided considering the collaboration, workspace, and contextual awareness perspectives. The results obtained were translated into an awareness support scale and three levels of quality were defined.